Wind Shear Effects in Convection–Permitting Models Influence MCS Rainfall and Forcing of Tropical Circulation - Ben Maybee; John H. Marsham; Cornelia M. Klein; Douglas J. Parker; Emma J. Barton; Christopher M. Taylor; Huw Lewis; Claudio Sanchez; Richard W. Jones; James Warner (Geophysical Research Letters, 2024)
Abstract Mesoscale Convective Systems (MCSs) play a critical role in tropical rainfall patterns and circulations. To reduce persistent biases and improve understanding of the climate system, international groups have called for unprecedented investment in global convection–permitting (CP) climate models. It is essential such models accurately represent MCSs, and in particular environmental interactions such as dynamical control by wind shear. We show that in representative current generation CP simulations, MCS updraft entrainment decreases with shear, leading to a realistic increase of extreme rainfall. We find the control of environmental shear extends to mean storm rainfall and anvil heights. The simulation of these effects depends strongly on model physics in both CP and parameterized models. We show that in West Africa, MCS shear response influences the zonal distribution of storm diabatic heating, modifying upscale impacts of convection. Our results demonstrate key tests for focused process–based assessment of CP model fidelity.